The Correlation between Physical Environmental Factors and the Occurrence of Leptospirosis (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Leptospirosis is a disease caused by a bacteria called Leptospira. Environmental risk factors for leptospirosis include biological, social, and physical (river or bodies of water, ditches, puddles, and the distance between the settlement area with garbage disposal area).This research aimed to determine the correlation between the physical environmental factors with the evidence of leptospirosis in Sukahaji Village, Babakan Ciparay District of Bandung City in 2017. The design of this research is a survey with cross-sectional approach. We used 100 population samples in this research. The Technique of obtaining data with observation sheet is using sheet checklist. We did univariate and multivariate data analysis using Chi square.The results showed that most ofÂ the population experienced leptrospirosis, and most of the physical environment such as rivers or bodies of water, ditches, puddles, and the distance between settlement area with the garbage disposal area are the risk factors of leptospirosis.